Relationship between nomophobia level and school success among university students - Özsavran, Musa; Kuzlu Ayyıldız, Tülay (Journal of Dependence, 2022)
Objective: This study aimed to determine any possible relationship between school success and nomophobia level among the university students. Method: This cross-sectional and descriptive type study was conducted during June 1-15, 2019 in the health vocational school of a state university located in Zonguldak city. Study data were collected by Student Information Form and Nomophobia Questionnaire (NMP-Q). Results: Nomophobia level was mild in 25.8%, moderate in 54.2% and severe in 19.8% of the students. Significant differences were found between some subscales and mean overall scale scores of the questionnaire based on the variables such as gender, daily frequency of checking smartphones, state of having a charger besides and checking the smartphone as soon as waking up. Conclusion: No significant diferences were found between Grade Point Average (GPA) of the students and their total and subscale scores from the questionnaire.